THE EFFECTS OF DIFFERENT GYMNASTICS TRAININGS ON BODY COMPOSITION AND SOME PERFORMANCE COMPONENTS IN ADULT MALE NON-GYMNASTS - Burak Gündoğan; Erkan Demirkan; Erbil Murat Aydın; Abdüsselam Turgut (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
The aim of this study was to compare the effects of artistic and trampoline gymnastics training on body composition and some of the physical fitness components in adult non-gymnasts.  Forty-eight adult non-gymnasts were randomly assigned to three groups: a trampoline gymnastics group (TG) (n = 16), an artistic gymnastics group (AG) (n = 16), and a control group (CG) (n = 16). Two of the group except the CG performed different gymnastics training, including artistic and trampoline gymnastics twice a week during 12 weeks. The control group performed only a warm-up exercise twice a week along the study. To determine the effects of each gymnastics training on body composition, Y dynamic balance test that including six postural tasks, vertical jump, standing long jump and two different flexibility tests, were performed before and after the study for all groups. The AG and TG were significantly (p<0,05) improved when it comes to all bio-motor abilities in adult non-gymnasts after 12 weeks of training. But the trampoline gymnastics exercises may be seen to be more efficient compared to the artistic gymnastics exercises. The trampoline exercises may be recommended as an alternative mode of exercise for improving bio-motor abilities.